STRATEGI PENILAIAN AUTENTIK KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI (STUDI KASUS DI SMP NEGERI 1 PABUARAN KABUPATEN CIREBON) - Halimi Ansor (Oasis : Jurnal Ilmiah Kajian Islam, 2018)
This study aims to describe the strategy of planning, implementing and evaluating the results of an authentic assessment of the 2013 curriculum for PAI (Islamic Studies) subjects and budi pekerti (ethics and character). This type of research is qualitative research. The subjects of the study were VII grade PAI teachers, grade VII guardians and Counseling Guidance teachers. Data collection through observation, interview, documentation study, and triangulation. Data analysis uses data reduction, data display, and conclusion drawing. The results of the study show: Planning an authentic assessment of the 2013 curriculum for PAI and Budi Pekerti subjects is still not optimal. Teachers of PAI subjects do not compile the midterm and daily assessment scores and do not plan portfolio assessments. The application of an authentic assessment of the 2013 PAI curriculum and Budi Pekerti has not run optimally. PAI subject teachers do not use observation sheets or journals and do not apply self-assessment, peer assessment, project appraisal, and portfolio assessment. Authentic assessment of the 2013 PAI and Budi Pekerti curriculum for 280 students. Assessment of attitudes for 27 students obtaining the category "Very Good", 251 students got "Good" grades and 2 students got the category "Enough". Assessment for knowledge competencies, range in value from 91-100 (2 students), 81-90 (48 students), and 71-80 (230 students), average score of 79 predicates C. Assessment of skills competency, range of grades 81-90 ( 88 students), and 71-80 (192 students), average score of 77, predicate C.Penelitian ini bertujuan untuk mendeskripsikan strategi perencanaan, penerapan dan hasil penilaian penilaian autentikÂ  kurikulum 2013 mata pelajaranÂ  PAI dan Budi Pekerti. Jenis Penelitian yang dilakukan adalah penelitian kualitatif. Subjek penelitian adalah guru PAI kelas VII, wali kelas VII dan guru Bimbingan Konseling. Pengumpulan data melalui observasi, wawancara, studi dokumentasi, dan triangulasi. Analisis data dengan menggunakan reduksi data, display data, dan penarikan kesimpulan. Hasil Penelitian menunjukkan: Perencanaan penilaian autentik kurikulum 2013 mata pelajaran PAI dan Budi Pekerti masih belum optimal. Guru PAI tidak menyusun kisi-kisi penilaian harian dan penilaian tengah semester dan tidakÂ  menyusun perencanaan penilaian portofolio. Penerapan penilaian autentik kurikulum 2013 PAI dan Budi Pekerti, belum berjalan secara optimal. Guru PAI tidak menggunakan lembar pengamatan atau jurnal danÂ  tidak menerapkan penilaian diri, penilaian antar teman, penilaian proyek,Â Â Â  dan penilaian portofolio.Hasil penilaian autentik kurikulum 2013 mata PAI dan Budi Pekeri diÂ  dari 280 siswa. Penilain sikap 27 siswa â€œAmat Baikâ€, 251 siswa â€œBaikâ€ dan 2 siswa â€œCukupâ€. Penilaian kompetesnsi pengetahuan, rentang nilai 91-100 (2 siswa),Â  81-90 (48 siswa), dan 71-80 (230 siswa), nilai rata-rata 79 predikat C. Penilaian kompetensi keterampilan, rentang nilai 81-90 (88 siswa), dan 71-80 (192 siswa), nilai rata-rata 77, predikat C.